1991
DOI: 10.1007/bf00197794
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic-acid metabolism in a wilty mutant of Nicotiana plumbaginifolia

Abstract: A mutant of Nicotiana plumbaginifolia, CKR1, isolated on the basis of its enhanced resistance to cytokinins was found to have a greater tendency to wilt than the wild type (Blonstein et al., 1991, Planta 183, 244-250). Further characterisation has shown that the wiltiness in the mutant is not caused by an insensitivity to abscisic acid (ABA) because the external application of ABA leads to stomatal closure and phenotypic reversion. The basal ABA level in the mutant is < 20% of that in the wild type. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…There are another two Arabidopsis genes with 46% similarity to the novel C-terminus of ABA3 which are 74% similar to each other, suggesting this domain is functionally important (possibly in determining target enzyme specificity). The flacca (flc) mutant of tomato may also be orthologous to aba3 and Npaba1 because all three mutants are ABAdeficient, cannot convert xanthoxal or ABA-aldehyde to ABA, lack AO and XDH but not NR activities, and in vitro sulfurylation with Na 2 S reactivates preexisting XDH and AO proteins in flc, and Npaba1, as in aba3, extracts Parry et al, 1991;Leydecker et al, 1995;Marin and Marion-Poll, 1997;Abaka et al, 1998;Sagi et al, 1999). The nar2a (Az34) MoCo mutant of barley lacks all AO, XDH and NR activities, suggesting an upstream lesion in the synthesis of the MoCo which all three enzyme activities require (Walker-Simmons et al, 1989;Rock, 1991).…”
Section: Late Specific Steps In Aba Biosynthesismentioning
confidence: 99%
“…There are another two Arabidopsis genes with 46% similarity to the novel C-terminus of ABA3 which are 74% similar to each other, suggesting this domain is functionally important (possibly in determining target enzyme specificity). The flacca (flc) mutant of tomato may also be orthologous to aba3 and Npaba1 because all three mutants are ABAdeficient, cannot convert xanthoxal or ABA-aldehyde to ABA, lack AO and XDH but not NR activities, and in vitro sulfurylation with Na 2 S reactivates preexisting XDH and AO proteins in flc, and Npaba1, as in aba3, extracts Parry et al, 1991;Leydecker et al, 1995;Marin and Marion-Poll, 1997;Abaka et al, 1998;Sagi et al, 1999). The nar2a (Az34) MoCo mutant of barley lacks all AO, XDH and NR activities, suggesting an upstream lesion in the synthesis of the MoCo which all three enzyme activities require (Walker-Simmons et al, 1989;Rock, 1991).…”
Section: Late Specific Steps In Aba Biosynthesismentioning
confidence: 99%
“…Instead, the mutant seems less able to mount a response to general stresses such as high cytokinin concentrations. The mutant has a wilty phenotype, shows little ABA induction following stress, and apparently is blocked in the last step of ABA biosynthesis (12).…”
Section: Cytokinin-resistant Mutantsmentioning
confidence: 99%
“…Another candidate for the t-XAN metabolite is t-ABA-alcohol. 191 It has been reported that both the wild type and wilty mutant of tobacco plants are endowed with this pathway from t- XAN;20) however, the level of t-ABA-alcohol is usually too low to be identified in wild tomato plants. 19 ) In conclusion, without any plausible metabolite having been found so far, it is difficult to explain the fate of t-XAN, suggesting that t-XAN does not actually exist in plants.…”
mentioning
confidence: 99%